A Review on Authentic Leadership and Employee Creativity - Khawar Hussain (Journal of Humanistic, Management and Social Science Review, 2024)
Based on the literature on the relationship between Authentic Leadership (AL) and employee creativity (EC), this article applies literature review method to explore the current situation of this issue. On the basis of comparative inquiry of relevant literature, this article present various definition of AL and EC proposed by different scholars and the importance of AL and EC for organization innovation and adaptation to change. It also synthesize existing research findings on the relationship between AL and EC.